Effect of contamination and relative humidity on the function of thyristor voltage monitoring board. (16th May 2022) - Liu, Zichen; Wang, Liming; Mei, Hongwei; Cao, Bin; Yin, Fanghui; Xu, Yongsheng; Zhang, Fuzeng; Jiang, Yi; Farzaneh, Masoud
Abstract: In recent years, shutdown accidents caused by thyristor voltage monitoring (TVM) board failure have occurred several times in converter stations. With the increase of operation time, the working reliability problem of TVM board becomes a challenge to the safe operation. This paper studies the effects of pollution severity and relative humidity ( RH ) on the function of TVM board. The results show that the increase of RH can lead to the advance or even disappearance of check‐back signals. Furthermore, the increase of pollution severity can decrease the failure RH threshold. Through simulation and equivalent experiment, it is verified that the resistance decrease of the voltage balancing resistor under the combined effect of contamination and RH is the main reason for the advance of check‐back signals. According to the experiments, it is found that the upper surface contamination has a greater effect on the function of TVM board than the lower surface contamination, resulting in more decrease of the failure RH threshold. In addition, leakage current at different RH is also measured. Results show that the pulse peak of leakage current is closely related to check‐back signals. When the pulse peak is too small or disappears, check‐back signals also disappear, indicating that the TVM board fails.